(untitled) (Journal of Geography and Environmental Management, 2020)
This article is based on the study of documents on administrative and territorial changes that took place in the territory of the Republic of Kazakhstan, as well as on statistical data of population censuses. The article deals with the issues of administrative-territorial changes on the map of Kazakhstan, provides a brief description of the administrative-territorial division (ATD) of the country in different periods of its formation and further development. Attention was drawn to certain changes that had taken place after obtaining the state independence of Kazakhstan, mainly related to changes in the functions performed in the new political and state structure and the names of regions, districts, cities and rural settlements in accordance with Article 9 of the Law of the Republic of Kazakhstan of December 8, 1993 y. «On the administrative-territorial structure of the Republic of Kazakhstan», which became the main document defining the legal basis for the vital activity of the territorial-administrativnoy system of the republic. The administrative-territorial system of Kazakhstan includes such administrative-territorial units as a village, village, rural district, a district in a city, a city, a rural area and a region. Also, the article considers new formations of administrative-territorial units, their abolition or restoration, renaming, and other issues of administrative-territorial changes on the political map of Kazakhstan and their causes.